Modernity and tradition in colombian art in mid-20th century: el dorado by eduardo ramírez villamizar. (2013)
In 1958, Eduardo Ramírez-Villamizar created the mostambitious public artwork to date in modern Colombia:El Dorado, an entirely gilded monumental mural for thenew International Style building of the Banco de Bogotá.This paper constitutes the first effort to contextualizeand analyze it while discussing the strategies used tointegrate pre-Columbian motifs within internationalgeometric art and addresses the implications of thisjuxtaposition within the artist’s aesthetic program. Italso examines the sources and context in which thework was produced, arguing that El Dorado marked theinstitutionalization of geometric abstraction as a symbolof modernization and progress in Colombian art, whileat the same time reviving local artistic traditions.